Architecting Dependable Systems VII - Casimiro, Antonio; de Lemos, Rogério; Gacek, Cristina (Programming and Software Engineering,, 2010)
As software systems become increasingly ubiquitous, issues of dependability become ever more crucial. Given that solutions to these issues must be considered from the very beginning of the design process, it is clear that dependability and security have to be addressed at the architectural level. This book, as well as its six predecessors, was born of an effort to bring together the research communities of software architectures, dependability, and security. This state-of-the-art survey contains expanded, peer-reviewed papers based on selected contributions from the Workshop on Architecting Dependable Systems (WADS 2009), held at the International Conference on Dependable Systems and Networks (DSN 2009), as well as a number of invited papers written by renowned experts in the area. The 13 papers are organized in topical sections on: mobile and ubiquitous systems, architecting systems, fault management, and experience and vision.